2019
DOI: 10.1097/bpo.0000000000001333
|View full text |Cite
|
Sign up to set email alerts
|

Olecranon Fractures in Pediatric Patients With Osteogenesis Imperfecta

Abstract: Background: Osteogenesis imperfecta (OI) is a hereditary disorder characterized by an abnormality of the quality or quantity of type I collagen, leading to bone fragility. Fractures in children with OI may result from minor trauma and have atypical patterns. Previous studies have found a strong relationship between olecranon fractures and OI in pediatric populations, but the characteristics of olecranon fractures within the OI patient population have not been fully described. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 14 publications
4
30
0
Order By: Relevance
“…Previous literature has established that patients with OI tend to sustain olecranon fractures under low-energy mechanisms 4–7,12. Our study supports these findings and we report a significant difference in mechanism of injury between OI and non-OI patients.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Previous literature has established that patients with OI tend to sustain olecranon fractures under low-energy mechanisms 4–7,12. Our study supports these findings and we report a significant difference in mechanism of injury between OI and non-OI patients.…”
Section: Discussionsupporting
confidence: 91%
“…It has been traditionally accepted that isolated fractures of the olecranon are pathognomonic for OI. 2,[4][5][6][7] A study by Zionts and Moon 4 found that only 5 of the 10 children who sustained an isolated olecranon fracture had received a diagnosis of OI before their first fracture, and therefore, recommended considering an OI diagnosis for any child presenting with an isolated, displaced olecranon fracture. However, Evans and Graham 11 reported only 6 of 57 patients with isolated olecranon fractures had a diagnosis of OI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations